Prediction of Material Requirements For Vocational Practices Using The Monte Carlo Method (Case Study at SMK Dwi Sejahtera Pekanbaru) - Suandi Daulay; Rahmi Rahmi (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Vocational High School (SMK), every practice always requires supporting materials. When the demand for these practice materials coincides between departments, so schools have difficulty in fulfilling them. The purpose of processing data on borrowing practice materials is to optimally meet the practical needs of the department. The data that is processed in this study is the data on demand for practice materials, data on practice needs and data on supply of practice materials. The data is processed using the Monte Carlo method with testing using PHP programming. The results of this study are predictions of the optimal practice material needs in the TKJ department and the materials that are needed and the amount of practice materials needed. 97% accurate. So that this research is very helpful in predicting the material needs of practice, this research is very helpful for the school in improfing services for student praticum.